Aggregate import demand and expenditure components in five ASEAN countries: an empirical study - Mohammad Haji Alias,; Tuck , Cheong Tang; Jamal Othman, (Penerbit Universiti Kebangsaan Malaysia, 2001)
This paper examines the long run relationship between aggregate imports and expenditure components of five ASEAN countries using Johansen multivariate cointegration analysis. The ASEAN-5 countries considered are Malaysia, Indonesia, the Philippines, Singapore and Thailand. Annual data for the period 1968-1998 are used with the exception of Singapore, with a shorter sample period, 1974-1998. The final demand expenditure variable is disaggregated into public and private consumption expenditure, investment expenditure and exports. The use of a disaggregated demand variable, as opposed to the use of a single demand variable, is justified by the possibility that each final demand component may have different import contents. The approach employed in this study avoids the problem of aggregation bias. The results of Johansen’s multivariate test reveal that import demand is cointegrated with its determinants for all ASEAN-5 countries. Short-run variations in import demand found to be influenced by variations in relative prices and macro components of final demand. Import demand is also found to be elastic with respect to relative prices for all ASEAN-5 countries except the Philippines. The findings provide a relevant for policy implications.